Bioethanol production from whey powder by immobilized E. coli expressing Vitreoscilla hemoglobin: optimization of sugar concentration and inoculum size. Issue 9 (21st October 2021) - Sar, Taner; Stark, Benjamin C.; Akbas, Meltem Yesilcimen
Abstract: A combined Vitreoscilla hemoglobin/immobilization system was evaluated for ethanol production using whey powder as a carbon source and ethanologenic E. coli strain FBR5 and its Vitreoscilla hemoglobin (VHb) expressing derivative strain, TS3. The effects of varying the inoculation concentration (5, 10, 20 or 30%) of alginate beads containing cells of either strain, and the lactose levels (8–15%) of whey powder media (WP8-WP15), were studied. Ethanol production was enhanced in strain TS3 compared to strain FBR5 for all combinations of inoculation size and medium lactose concentration. This enhancement increased from 41% to 83% with an 8–15% increase in lactose concentration. The maximum amount of ethanol, 4.64% (v/v) with 99% fermentation efficiency, was produced after growth for 72 h by immobilized strain TS3, using 10% bead inoculation and medium containing 8% lactose.